Complete polyp resection with cold snare versus hot snare polypectomy for polyps of 4–9 mm: a randomized controlled trial - Pedersen, Ina B.; Rawa-Golebiewska, Anna; Calderwood, Audrey H.; Brix, Lone D.; Grode, Louise B.; Botteri, Edoardo; Bugajski, Marek; Kaminski, Michal F.; Januszewicz, Wladyslaw; Ødegaard, Hjalmar; Kleist, Britta; Kalager, Mette; Løberg, Magnus; Bretthauer, Michael; Hoff, Geir; Medhus, Asle; Holme, Øyvind (Endoscopy, 2022)
Background Endoscopic screening with polypectomy reduces the incidence of colorectal cancer (CRC). Incomplete polyp removal may attenuate the effect of screening. This randomized trial compared cold snare polypectomy (CSP) with hot snare polypectomy (HSP) in terms of complete polyp resection.Methods We included patients ≥ 40 years of age at eight hospitals in four countries who had at least one non-pedunculated polyp of 4–9 mm detected at colonoscopy. Patients were randomized 1:1 to CSP or HSP. Biopsies from the resection margins were obtained systematically after polypectomy in both groups. We hypothesized that CSP would be non-inferior to HSP, with a non-inferiority margin of 5 %. Logistic regression models were fitted to identify the factors explaining incomplete resection. Results 425 patients, with 601 polyps, randomized to either CSP or HSP were included in the analysis. Of 318 polyps removed by CSP and 283 polyps removed by HSP, 34 (10.7 %) and 21 (7.4 %) were incompletely resected, respectively, with an adjusted risk difference of 3.2 % (95 %CI −1.4 % to 7.8 %). There was no difference between the groups in terms of post-polypectomy bleeding, perforation, or abdominal pain. Independent risk factors for incomplete removal were serrated histology (odds ratio [OR] 3.96; 95 %CI 1.63 to 9.66) and hyperplastic histology (OR 2.52; 95 %CI 1.30 to 4.86) in adjusted analyses. Conclusion In this randomized trial, non-inferiority for CSP could not be demonstrated. Polyps with serrated histology are more prone to incomplete resection compared with adenomas. CSP can be used safely for small polyps in routine colonoscopy practice.